PERAN TAFSIR AL-QUR’AN TERHADAP PEMAHAMAN SISWA DALAM PEMBELAJARAN AJARAN ISLAM - Kurniasih, Dede Dwi; Suratin, Sonia Isna; Devi, Yulia Nurmasita; Fakhrurridha, Hujjatul (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study examines the role of Qur'anic interpretation in improving students' understanding of Islamic teachings, focusing on students' lack of in-depth understanding of the context and meaning of Qur'anic verses. This study aims to highlight the important role of interpretation in the context of Islamic education, focusing on how interpretation can be an effective tool in improving students' understanding and engagement. Using a qualitative approach, this study collected data through a literature review and analysis of relevant interpretation documents. The results show that Qur'anic interpretation can be an effective tool in learning, improving students' knowledge, and encouraging active engagement and critical thinking. Interpretation serves as a bridge between the sacred text and the realities of life, strengthening students' spiritual and moral foundations. Thus, Qur'anic interpretation serves as a bridge connecting the sacred text with the realities of life, strengthening students' spiritual and moral foundations in understanding and practicing Islamic teachings comprehensively. These findings emphasize the importance of integrating interpretation into the Islamic education curriculum to achieve a more comprehensive understanding among students. The results of this study are expected to make a significant contribution to the development of Islamic teaching teaching methods in schools.